Analisis Tingkat Kepuasan Konsumen terhadap Kualitas Produk Honda Merek Vario - Kusumawati, Baiq Diah (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2021)
The purpose of this study is to know the level of consumer satisfaction with the quality of products (appearance, characteristics, reliability, durability, service, aesthetics, and perception of quality) attached to the Honda Vario and to know which of the seven dimensions of product quality (appearance, characteristics, reliability, durability, service, aesthetics, and perception of quality) attached to the Honda Vario provide the most optimal satisfaction. The type of research used is associative research with sample survey method. Determination of the number of respondents is determined by slovin formula, then the taking of respondents using stratified proportional random sampling techniques. This study used 84 respondents who are buyers and users of Honda Vario. The method of data collection using questionnaires, then as a tool of analysis of the author's data using the Consumer Satisfaction Index and Cartesian Diagram. Based on the analysis can be concluded: 1) The level of consumer satisfaction to the quality of products attached to the Honda Vario based on overall GPA in accordance with the consumer response is stated to be very good or very satisfactory; 2) Of the seven dimensions of product quality that provide the most optimal satisfaction based on cartesian diagrams, namely: characteristics, reliability, service, aesthetics and perception of quality. By looking at respondents' responses about the quality dimension of the product attached to the Honda Vario, it is necessary to improve the quality of the product in order to provide higher satisfaction in the future